Environmental Regulation and Employment in Resource-Based Cities in China: The Threshold Effect of Industrial Structure Transformation - Qin, Bingtao; Liu, Lei; Yang, Le; Ge, Liming (Frontiers in Environmental Science, 2022)
Resource-based cities in China face the dual pressure of environmental pollution and unemployment. Therefore, it is necessary to measure the effect of environmental regulation on employment. In this study, we first analyzed the theoretical mechanism of employment effects of environmental regulation. Second, we constructed a nonlinear panel threshold regression model with industrial structure rationalization and optimization as the threshold variables and used data from 115 resource-based prefecture-level cities to empirically examine the impact of environmental regulation on employment. The results demonstrate that 1) There is a significant threshold effect between environmental regulation and employment in resource-based cities, with the rationalization and optimization of the industrial structure gradually crossing the threshold from a low threshold to a high threshold, and the impact of environmental regulation on employment has gradually changed from an inhibitory effect to a promotion effect; 2) This conclusion still holds after the robustness test and the division of life cycles of different types of resource-based cities; 3) The coal resource cities as a representative of this kind of resource-based cities with serious environmental pollution, strengthening environmental regulation, have an obvious role in promoting employment. This study enriches the research content of environmental regulation on employment and provides useful references for rational improvement of unemployment in China.